PENGARUH LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BELAJAR SERTA IMPLIKASINYA PADA HASIL BELAJAR SISIWA MATA PELAJARAN EKONOMI - Andini, Wanda; Yoni Hermawan; Edi Fitriana Afriza (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research was motivated by the low learning outcomes of students which were caused by students' decreased learning motivation. This can be seen from the results of the PAS score which is still below the KKM in economics subjects, thus showing that student learning outcomes are still low. This research aims to measure how much influence the school environment has on learning motivation and its implications for student learning outcomes directly and indirectly. This research is quantitative research using a survey method with an explanatory design. The population of this study were all students in classes X and XI, totaling 642. The sampling technique was probability sampling using simple random sampling. The sample taken was 246 students. Data was obtained from the results of distributing questionnaires and analyzed using path analysis with the help of SPSS version 23. The results of research on direct influence show that the school environment influences learning motivation, the school environment influences learning outcomes and learning motivation influences learning outcomes. Then, the results Research on indirect effects shows that the school environment influences learning outcomes through learning motivation